Osteopetrosis and Hip Fracture. Case Report and Literature Review - Liyanira Alonso Leiva; José Julio Requeiro Molina; Ana María Machado Consuegra (Revista Finlay)
Osteopetrosis constitutes a group of genetic disorders that determine skeletal sclerosis. It is also known as Albers-Schonberg disease. It is transmitted in both an autosomal dominant and recessive manner. Its early diagnosis makes it possible to treat the underlying pathology and the fracture early, in order to achieve bone consolidation and incorporate patients into their daily lives with a favorable evolution. We present the case of a 10-year-old female patient, white-skinned, who had been in consultation at the Frank País García International Orthopedic Scientific Complex since she was 4 years old, where she was diagnosed with osteopetrosis. Six years later, he fell off his feet and sustained trauma to his right hip. It started with severe pain, swelling and difficulty walking. The patient attended the Paquito González Cueto Pediatric University Hospital in Cienfuegos where she was evaluated by pediatric, orthopedic and traumatology specialists. A hip x-ray was performed where the diagnosis of right hip fracture was confirmed, for which he was admitted for surgical treatment. The case is presented with the objective of exposing the approach to this type of disease and the treatment method, motivated by its low frequency of presentation.